Kebijakan Pemerintah Dalam Menangani Anak Yatim Piatu Terhadap Korban Covid-19 di Kota Tangerang - Hafidati, Putri; Aziz, Hasnah (Universitas Medan Area, 2023)
This research was carried out to improve the welfare of orphans who have changed due to the Covid-19 pandemic which began in early 2020. Many fathers (orphans), mothers (orphans), or fathers and mothers (orphans) have died from Covid-19. The ongoing pandemic has an impact on increasing the number of children whose parents have died, as a result, stakeholders need to pay attention to the end. The inventory of laws and regulations on orphan health insurance for COVID-19 victims at the national and regional levels is the main focus. Research methods are juridical normative. Analytical and descriptive research is used in this study to describe laws and regulations that apply to legal theories and practices of positive law application. Based on the results of the analysis health insurance participants on behalf of orphans for health insurance, education, and protection are not expressly mentioned in laws or regulations related to child protection policies during the Covid-19 pandemic. This study suggests that the Government emphasizes the role of the state in protecting children, including children affected by COVID-19, by issuing Government Regulation (PP) Number 1. Children can be protected from the COVID-19 pandemic by maintaining their health and making efforts to create and maintain an environment that supports their growth and development